Microneedle-Based Approaches for Skin Disease Treatment - Yanhua Han; Xiaoyu Qin; Weisen Lin; Chen Wang; Xuanying Yin; Jiaxin Wu; Yang Chen; Xiaojia Chen; Tongkai Chen (Nano-Micro Letters, 2025)
Highlights Microneedles (MNs) are used extensively for treating skin diseases due to their capability to provide less-invasive targeted drug delivery. Intelligent MNs can be fabricated from biocompatible materials with specialized properties, thereby providing improved treatment efficacy. Currently, there are limitations in the clinical application of MNs, highlighting the significance of further investigation to facilitate the translation of this innovative technology into patient treatment contexts.